(untitled) (Journal of the Bangladesh Agricultural University, 2025)
Freshwater unionid mussels have a unique life cycle with glochidia larval occurrence for certain period in the suprabranchial chamber of females may have effect on condition index of the brood. Current study reports temporal changes in glochidia larval occurrence and its effect on condition index (CI) of freshwater mussel, Lamellidensjenkinsianus collected monthly over a year from a lentic habitat Darikathal Beel, Trishal, Mymensingh of Bangladesh during January to December 2023. Microscopic observation of the gonadal smears revealed an overall male-female sex ratio of 1:0.90, which did not deviate significantly from the expected 1:1 ratio. Glochidia larvae were present in the gills of females during February to July, September, and December. Majorityof the females (>75%) contained larvae in their gills during February, May and December. No glochidia larva was observed during August, October, and November indicated that larval shedding could have been completed before those months. Condition index (CI) of the mussels was the highest in February; indicating ideal time of harvesting from the habitat. In the current study, no noticeable difference in CIs of males, females without glochidia, and females with glochidia was reported over the study period. Therefore, it can be concluded that glochidia larval occurrence have no impact on condition index of L. jenkinsianus. J Bangladesh Agril Univ 23(2): 241-249, 2025